Caracterização genética e in situ de Gossypium barbadense na região norte do Brasil - Almeida, Vanessa Cavalcante de (2007)
Brazil has been considered one of the diversity centers of Gossypium barbadense species. It is believed that a relatively big erosion genetic process occurs with the species, due to economic, cultural and agricultural problems. A local diagnostic about species situation is the first step for reducing the diversity loss and establishing conservation strategies in situ. This research aimed the identification of the presence of Gossypium populations, characterization, determination of the main risks and collection of the accesses to store in germoplam banks, in Para and Amapa States. Expeditions were conducted in November 2004. An interview was carried out with the plant proprietor for characterizing in situ of G. barbadense species and of the environment where the plants were inserted. On hundred seventy nine plants in 22 municipal districts were collected in Para State and 117 plants in nine municipal districts in Amapa State. The majority of plants belong to G. barbadense species (98% in Amapa and 94% in Para). Plants occur in back yards, beside roads and spontaneously. That ones from back yards were more abundant (97% in Amapa and 95% in Para) and maintained as medicinal plants as the principal reason. Plants in natural environments in both states evaluated were not found, therefore, the creation of reserves and the application of others conventional methods of maintenance in situ are not applicable. The plant proprietors do not use to store or process seeds. Seed storage was reported as a practice by only 1% of the plant proprietors from Para and 11% from Amapa. The most plants collected were from two to three years of age (58% in Amapa and 93% in Para). As conclusions G. barbadense is the species most spread in the two studied states and are found in back yards. In Amapa State the botanical variety barbadense or Quebradinho is predominant, whereas in Para State the predominant variety is brasiliense or Rim-de-boi. Adequate conservation of thestudied species must be carried out in germoplasm collections maintained ex situ